Persistent opioid use and opioid-related harm after hospital admissions for surgery and trauma in New Zealand: a population-based cohort study - Peter Jones; Matthew Moore; Amy Hai Yan Chan; Chris Frampton; Doug Campbell; Jiayi Gong; Alan Forbes Merry; Kebede A Beyene; John McCall (BMJ Open)
Introduction Opioid use has increased globally for the management of chronic non-cancer-related pain. There are concerns regarding the misuse of opioids leading to persistent opioid use and subsequent hospitalisation and deaths in developed countries. Hospital admissions related to surgery or trauma have been identified as contributing to the increasing opioid use internationally. There are minimal data on persistent opioid use and opioid-related harm in New Zealand (NZ), and how hospital admission for surgery or trauma contributes to this. We aim to describe rates and identify predictors of persistent opioid use among opioid-naïve individuals following hospital discharge for surgery or trauma.Methods and analysis This is a population-based, retrospective cohort study using linked data from national health administrative databases for opioid-naïve patients who have had surgery or trauma in NZ between January 2006 and December 2019. Linked data will be used to identify variables of interest including all types of hospital surgeries in NZ, all trauma hospital admissions, opioid dispensing, comorbidities and sociodemographic variables. The primary outcome of this study will be the prevalence of persistent opioid use. Secondary outcomes will include mortality, opioid-related harms and hospitalisation. We will compare the secondary outcomes between persistent and non-persistent opioid user groups. To compute rates, we will divide the total number of outcome events by total follow-up time. Multivariable logistic regression will be used to identify predictors of persistent opioid use. Multivariable Cox regression models will be used to estimate the risk of opioid-related harms and hospitalisation as well as all-cause mortality among the study cohort in a year following hospital discharge for surgery or trauma.Ethics and dissemination This study has been approved by the Auckland Health Research Ethics Committee (AHREC- AH1159). Results will be reported in accordance with the Reporting of studies Conducted using Observational Routinely collected health data statement (RECORD).